Cuban foreign policy - Falk, Pamela S. (Lexington Books LexingtonUS, 1986)
Gives history of Cuban foreign relations through the periods of Spanish, American and Soviet dependance. Shows how other nations view Cuba's foreign adventures and documents her foreign programs. Discusses Cuba's relations in the Western hemisphere. Looks at its assistance to insurgency movements; its African assistance programs; and its international economic policy and decision making.